(untitled) (International relations and international law Journal, 2023)
When discussing the issue of impunity, the ICL academia lacks attention to the concept of “impunity”. The understanding of the concept of impunity is limited to its damage to the value and function of criminal law, and ignores the ontological significance of the principle of equality to it. Therefore, it is impossible to explain the fundamental reason why the ICC cannot “end the history of impunity”. This paper examines the three dimensions of “impunity”. First of all, in the ontological dimension, this paper points out that impunity should be interpreted at “thick” and “thin” levels: “Thin impunity” focuses on the value and punishment function of ICL; “Thick impunity” means that the root cause of impunity is the failure to guarantee “equality before the law”. Secondly, from the perspective of epistemology, it is pointed out that the reason why the ICC can’t guarantee equality before the law lies in the “selectivity” of the court – “legal selectivity” and “political selectivity”. Finally, from the perspective of methodology, it is pointed out that the current situation of the international society in the horizontal/vertical dual structure and the structural defects of the Court decide that the ICC can’t end the impunity caused by the “absence of equality”, and advocates the introduction of the pioneering but little-known “International Commission against Impunity in Guatemala (CICIG)” model, which provides an effective way to solve the problem of impunity. Key words: Impunity; Equality; ICC; Rule of Law; Selectivity; CICIG mode